1996
DOI: 10.1093/infdis/174.4.752
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Invasive Pneumococcal Disease in Southern California: Implications for the Design and Conduct of a Pneumococcal Conjugate Vaccine Efficacy Trial

Abstract: Population-based prospective surveillance of invasive pneumococcal disease was done in Southern California from 31 March 1992 to 1 April 1995; 814 cases were identified, for an incidence of 12.5/100,000 persons/year. The incidence among persons < or = 2, < or = 5, and > or = 65 years of age was 145, 72, and 32/100,000, respectively. More than 95% of cases included bacteremia; incidence of meningitis was 0.8/100,000. Among children < or = 2 years of age, 79% of isolates were obtained in the outpatient setting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
75
1
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(88 citation statements)
references
References 41 publications
8
75
1
4
Order By: Relevance
“…In the United States, pneumococcus causes 50,000 cases of bacteremia and 3,000 cases of meningitis annually (2,3). Faced with one of the most frequent nasopharyngeal colonizers of children, the host immune response can be assumed to play an important role in preventing the progression from colonization to invasive pneumococcal disease.…”
mentioning
confidence: 99%
“…In the United States, pneumococcus causes 50,000 cases of bacteremia and 3,000 cases of meningitis annually (2,3). Faced with one of the most frequent nasopharyngeal colonizers of children, the host immune response can be assumed to play an important role in preventing the progression from colonization to invasive pneumococcal disease.…”
mentioning
confidence: 99%
“…2,3 By 1999, 38% of laboratory isolates in children who were younger than 2 years were nonsusceptible to penicillin, 4 with higher rates reported in local areas. [5][6][7] In February 2000, heptavalent pneumococcal conjugate vaccine (PCV7) was released to provide immunity to the 7 serotypes responsible for 85% of pediatric invasive pneumococcal disease 8 and 78% of penicillin-nonsusceptible S pneumoniae (PNSP) isolates in children. 9 Prelicensure trials showed a 90% reduction in invasive disease 10 and a 23% reduction in all-cause pneumonia in the first 2 years of life.…”
mentioning
confidence: 99%
“…[1][2][3] Resistance among Streptococcus pneumoniae is of particular concern 4,5 because this organism is the leading cause of meningitis 6 and other serious bacterial infections 7 in children, as well as a major cause of more common localized infections such as otitis media. 8 Penicillin-nonsusceptible S pneumoniae (PNSP) have become increasingly common in the United States over the past decade.…”
mentioning
confidence: 99%